Uso de alimento balanceado con alto contenido proteínico en diferentes etapas de gestación luego del empadre en cuyes (cavia porcellus) hembras gestantes, en el criadero auqui cuy, Salinas de Ibarra - Sevilla Moncayo, Nicole Gabriela (2014)
In hatchery of Auquicuy, located in Salinas de Ibarra, Ecuador. The use of balanced food with high protein content 20% was evaluated in different stages of gestation, T0: 42 days T1: 49 days and T2: 56 days, after the controlled breeding program with 214 pregnant female guinea pigs. The optimal time to transfer of the female guinea pig to the individual place where she is going to give birth was evaluated in order of each treatment. T0, T1, T2. In to the technic breeding system. By indicators of reproductive parameters such us: Difficult births, abortions, litter size at birth, number of stillbirths, mummified number of births, birth litter weight, litter weaning weight, infant mortality and breeding, number stillborn, litter weight at weaning...